The Cytokinin Complex Associated With Rhodococcus fascians: Which Compounds Are Critical for Virulence? - Jameson, Paula E.; Dhandapani, Pragathi; Song, Jiancheng; Zatloukal, Marek; Strnad, Miroslav; Remus-Emsermann, Mitja N. P.; Schlechter, Rudolf O.; Novák, Ondrej (Frontiers in Plant Science, 2019)
Virulent strains of Rhodococcus fascians cause a range of disease symptoms, many of which can be mimicked by application of cytokinin. Both virulent and avirulent strains produce a complex of cytokinins, most of which can be derived from tRNA degradation. To test the three current hypotheses regarding the involvement of cytokinins as virulence determinants, we used PCR to detect specific genes, previously associated with a linear virulence plasmid, including two methyl transferase genes (mt1 and mt2) and fas4 (dimethyl transferase), of multiple strains of R. fascians. We inoculated Pisum sativum (pea) seeds with virulent and avirulent strains of R. fascians, monitored the plants over time and compared these to mock-inoculated controls. We used RT-qPCR to monitor the expression of mt1, mt2 and fas4 in inoculated tissues and LC-MS/MS to obtain a comprehensive picture of the cytokinin complement of inoculated cotyledons, roots and shoots over time. The presence and expression of mt1 and mt2 was associated with those strains of R. fascians classed as virulent, and not those classed as avirulent. Expression of mt1, mt2 and fas4 peaked at nine days post inoculation (dpi) in cotyledons and at 15 dpi in shoots and roots developed from seeds inoculated with virulent strain 602. Pea plants inoculated with virulent and avirulent strains of R. fascians both contained cytokinins likely to have been derived from tRNA turnover including the 2-methylthio cytokinins and cis-zeatin-derivatives. Along with the isopentenyladenine-type cytokinins, the levels of these compounds did not correlate with virulence. Only the novel 1- and 2-methylated isopentenyladenine cytokinins were uniquely associated with infection by the virulent strains and are, therefore, the likely causative factors of the disease symptoms.